Effect of nanostructured grains in co-sputtered Ni-GDC thin-film anode on methane conversion kinetics for low temperature solid oxide fuel cells operating on nearly dry methane. Issue 7 (1st April 2022) - Choi, In Won; Yu, Wonjong; Ryu, Sangbong; Lee, Sanghoon; Cha, Suk Won; Cho, Gu Young
Abstract: Direct-methane solid oxide fuel cells (DMSOFCs) have recently attracted substantial attention due to their simplified system, reduced cost, and the direct availability of methane fuel obtained from natural gas. Among oxygen-ion conductive materials, doped-ceria such as gadolinium-doped ceria (GDC) or samarium-doped ceria can be incorporated into Ni-based anodes to reinforce their coking resistance, enlarge their electrochemical reaction area, and improve the kinetics of the internal reforming/electrochemical oxidation of methane. To reduce the range of operating temperatures of DMSOFCs while maintaining their performance, the thin film deposition technique of magnetron sputtering was adopted in this work. An Ni-GDC thin-film anode and a Pt thin-film cathode were deposited on scandia-stabilized zirconia (ScSZ) electrolyte supports. This fuel cell was tested with directly supplied methane fuel (3% H2 O) at 500 °C. The results demonstrated the effects of the GDC volume fraction in the anode—which was controlled by co-sputtering power—on open circuit voltage and electrochemical performance. The co-sputtered Ni-GDC anode was able to survive through 36-h operation, although there was some performance degradation. Field-emission scanning electron microscopy results revealed no formation of filamentous carbon on the Ni catalysts, despite the fact that both X-ray photoelectron spectroscopy and Raman spectroscopy analyses detected carbon coking. The relatively high performance and resistance to carbon coking of co-sputtered thin-film anode were attributed to its intrinsic small grain size.